Radical Ecology and Conservation Science: An Australian Perspective. (1st June 1998) - Robin, Libby
Abstract : Histories of environmentalism in Australia often overlook the 1950s, an era when scientific ecology dominated environmental activism. The political work of A.B. Costin in the CSIRO Alpine Ecology Unit in the Snowy Mountains, New South Wales, is examined closely as an example of how a scientist working within the limited institutional structures available to ecologists was able to defend natural areas against formidable odds. The successes of the 1950s established the credibility of science and scientists in conservation matters in the 1960s and later. When radical environmentalism emerged in the late 1970s, many scientific ecologists were angry or hurt about the fact that they became distanced from political power, and some have adopted backlash positions as a result. The history of the involvement of scientific ecologists in political activism in the 1950s sheds light on their reactions to radical environmentalism as it emerged later.